Negative ion earplug composite material and preparation method thereof
By attaching cysteine to graphene and using ball milling technology to promote the attachment of negative ion powder, a modifier combining carbon-sulfur bonds and hydroxyl groups forms a self-healing Schiff base compound, which solves the problem of dispersion and stability caused by the agglomeration of negative ion powder. It solves the problem of poor performance and achieves the sustained release effect of negative ions and the improvement of the mechanical properties of composite materials.
Patent Information
- Application Number
- CN202411841606.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Negative ion powders are prone to agglomeration in practical applications, resulting in poor dispersion and stability, affecting the performance of negative ion products.
Attach cysteine to graphene, and use ball milling to promote the attachment of negative ion powder into the pore structure of graphene. At the same time, carbon-sulfur bonds and hydroxyl modifiers are used to modify cinnamic aldehyde and cysteine to form a self-healing Schiff Alkaline compounds improve the mechanical properties of composite materials.
The sustained release effect of negative ions is achieved, and the deformation recovery strength and mechanical properties of the composite material are significantly improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative ion earplug materials and relates to a negative ion earplug composite material and a preparation method thereof. Background Art
[0002] Negative ions have many positive effects on human health, so a variety of negative ion products have emerged on the market. These products include earplugs, health underwear, negative ion plastics and functional coatings, all of which are made from negative ion powders that can continuously release negative ions. These negative ion powders are processed by composite processing with polymer matrices such as fibers, plastics and coating resins to form various products with negative ion functions. Negative ion powder is actually an ultrafine mineral powder that contains a variety of elements and has a strong polarity on its surface, which makes it easy to agglomerate. Due to its strong surface polarity and poor interfacial affinity with polymers, in practical applications, single ultrafine negative ion powder particles cannot exist stably and often agglomerate by mutual attraction, thereby reducing its surface energy to form a stable state. However, after agglomeration, the performance of the ultrafine powder will deteriorate, which is not conducive to the performance of the negative ion powder. The dispersion and dispersion stability of the negative ion powder directly affect the final quality and various properties of the negative ion product. In order to overcome this problem, the surface of the negative ion powder must be modified to improve its dispersibility and stability in various matrices. Summary of the invention
[0003] The purpose of the present invention is to provide a negative ion earplug composite material and a preparation method thereof. The present invention achieves the sustained release effect of negative ions by attaching cysteine on graphene and then promoting the attachment of negative ion powder to the pore structure of graphene by ball milling. Then, cinnamaldehyde modified by thioglycerol with carbon-sulfur bonds and a large number of hydroxyl groups and cysteine form a self-repairing Schiff base compound, thereby improving the deformation recovery strength of the composite material and significantly improving the mechanical properties of the composite material.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a negative ion earplug composite material comprises the following steps: Step S1: Under an inert atmosphere, polyester polyol, isocyanate, N,N-dimethylacetamide and a catalyst are stirred and mixed to obtain a premix; Step S2: adding the modified particles to the premix and treating it at a constant temperature, then cooling it down and adding triethylamine and stirring it to obtain the product.
[0005] As a preferred technical solution of the present invention, the mass ratio of the polyester polyol, isocyanate, N,N-dimethylacetamide, catalyst, modified particles and triethylamine is 55-58:32-33:2.0-2.2:3.0-3.3:12-15:4.4-5.0; the catalyst is dibutyltin dilaurate; the isocyanate is a mixture of HDI and MDI in a mass ratio of 1:2; the polyester polyol is polytetramethylene ether polyol with a molecular weight of 2000.
[0006] As a preferred technical solution of the present invention, in step S1, the inert atmosphere is a nitrogen atmosphere; the stirring and mixing is stirring at a speed of 600-800 r / min for 15-20 min.
[0007] As a preferred technical solution of the present invention, in step S2, the constant temperature treatment is to maintain the temperature at 80-90°C for 1.5-2.0h; the cooling is to cool to 50-60°C; the stirring treatment is to stir at 500-600r / min for 40-50min.
[0008] As a preferred technical solution of the present invention, the method for preparing the modified particles comprises the following steps: Step 1: After the graphene and cysteine solution are ultrasonically treated, the negative ion powder is slowly added, and after the addition is completed, ball milling is performed, and then filtering and drying are performed to obtain composite particles; Step 2: After isopropanol and cinnamaldehyde are stirred and mixed, thioglycerol and an initiator are added, and then subjected to ultraviolet irradiation treatment and rotary evaporation to obtain a modified monomer; Step 3: Mix the composite particles and the isopropanol solution, add the modified monomer after temperature control and stir to obtain modified particles.
[0009] As a preferred technical solution of the present invention, in step one, the ultrasonic treatment is performed at a frequency of 300-400W for 40-50min; the ball milling is performed at 50-60r / min for 1.8-2.0h; the drying is performed at a temperature of 80°C to constant weight; and the mass ratio of the graphene, cysteine solution and negative ion powder is 8-10:40-50:1.8-2.0.
[0010] As a preferred technical solution of the present invention, in step 1, the cysteine solution is prepared by mixing cysteine and deionized water in a mass ratio of 3.0-3.2:100; the negative ion powder is prepared by mixing magnesium tourmaline and magnetite powder in a mass ratio of 2.5:3.0-3.3.
[0011] As a preferred technical solution of the present invention, in step 2, the initiator is photoinitiator 1173; the thioglycerol is 1-thioglycerol; the mass ratio of isopropanol, cinnamaldehyde, thioglycerol and initiator is 6-8:12-14:6.8-7.2:0.32-0.34.
[0012] As a preferred technical solution of the present invention, in step 2, the stirring and mixing is performed at a speed of 400-500 r / min for 30-40 min; and the ultraviolet irradiation treatment is performed at a wavelength of 365 nm for 1.5-2.0 h.
[0013] As a preferred technical solution of the present invention, in step three, the temperature of the temperature control is 20-24°C; the stirring treatment is stirring at a speed of 200-300 r / min for 8-10 hours.
[0014] As a preferred technical solution of the present invention, in step three, the isobutanol solution is prepared by mixing isobutanol and deionized water in a mass ratio of 4:1; the mass ratio of the composite particles, the isobutanol solution and the modified monomer is 18-20:60-70:3-4.
[0015] As a preferred technical solution of the present invention, a negative ion earplug composite material is prepared by the above preparation method.
[0016] Beneficial effects of the present invention: The present invention achieves the sustained release effect of negative ions by attaching cysteine on graphene and then promoting the attachment of negative ion powder to the pore structure of graphene by ball milling. Then, cinnamaldehyde modified by thioglycerol with carbon-sulfur bonds and a large number of hydroxyl groups and cysteine form a self-repairing Schiff base compound, thereby improving the deformation recovery strength of the composite material and significantly improving the mechanical properties of the composite material. DETAILED DESCRIPTION
[0017] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments. Example 1
[0018] A method for preparing a negative ion earplug composite material comprises the following steps: Step S1: in an inert atmosphere, polyester polyol, isocyanate, N,N-dimethylacetamide and a catalyst are stirred and mixed to obtain a premix; the inert atmosphere is a nitrogen atmosphere; the stirring and mixing is stirring at a speed of 600 r / min for 15 minutes; Step S2: adding the modified particles to the premix and subjecting it to constant temperature treatment, cooling it down and adding triethylamine and stirring it, thereby obtaining the product; the constant temperature treatment is to keep the temperature at 80° C. for 1.5 hours; the cooling is to cool the temperature to 50° C.; the stirring treatment is to stir at a speed of 500 r / min for 40 minutes; In steps S1-S2, the mass ratio of the polyester polyol, isocyanate, N,N-dimethylacetamide, catalyst, modified particles and triethylamine is 55:32:2.0:3.0:12:4.4; the catalyst is dibutyltin dilaurate; the isocyanate is a mixture of HDI and MDI in a mass ratio of 1:2; the polyester polyol is polytetramethylene ether polyol with a molecular weight of 2000.
[0019] The preparation method of the modified particles comprises the following steps: Step 1: After the graphene and cysteine solution are ultrasonically treated, the negative ion powder is slowly added, and after the addition is completed, ball milling is performed, and then filtering and drying are performed to obtain composite particles; Step 2: After isopropanol and cinnamaldehyde are stirred and mixed, thioglycerol and an initiator are added, and then subjected to ultraviolet irradiation treatment and rotary evaporation to obtain a modified monomer; Step 3: Mix the composite particles and the isopropanol solution, add the modified monomer after controlling the temperature, and stir to obtain modified particles; In step 1, the ultrasonic treatment is performed at a frequency of 300 W for 40 minutes; the ball milling is performed at 50 r / min for 1.8 hours; the drying is performed at a temperature of 80° C. to a constant weight; the mass ratio of the graphene, the cysteine solution and the negative ion powder is 8:40:1.8; the cysteine solution is prepared by mixing cysteine and deionized water at a mass ratio of 3.0:100; the negative ion powder is prepared by mixing magnesium tourmaline powder and magnetite powder at a mass ratio of 2.5:3.0; In step 2, the initiator is photoinitiator 1173; the thioglycerol is 1-thioglycerol; the mass ratio of isopropanol, cinnamaldehyde, thioglycerol and initiator is 6:12:6.8:0.32; the stirring and mixing is stirring at a speed of 400 r / min for 30 minutes; and the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 1.5 hours.
[0020] In step three, the temperature of the temperature control is 20° C.; the stirring treatment is stirring at a speed of 200 r / min for 8 hours; the isobutanol solution is prepared by mixing isobutanol and deionized water in a mass ratio of 4:1; the mass ratio of the composite particles, the isobutanol solution and the modified monomer is 18:60:3. Example 2
[0021] A method for preparing a negative ion earplug composite material comprises the following steps: Step S1: in an inert atmosphere, polyester polyol, isocyanate, N,N-dimethylacetamide and a catalyst are stirred and mixed to obtain a premix; the inert atmosphere is a nitrogen atmosphere; the stirring and mixing is stirring at a speed of 700 r / min for 18 minutes; Step S2: adding the modified particles to the premix and subjecting it to constant temperature treatment, cooling it down and adding triethylamine and stirring it to obtain the product; the constant temperature treatment is to keep the temperature at 85°C for 1.8h; the cooling is to cool it down to 55°C; the stirring treatment is to stir at a speed of 550r / min for 45min; In steps S1-S2, the mass ratio of the polyester polyol, isocyanate, N,N-dimethylacetamide, catalyst, modified particles and triethylamine is 56:32.5:2.1:3.2:14:4.7; the catalyst is dibutyltin dilaurate; the isocyanate is a mixture of HDI and MDI in a mass ratio of 1:2; the polyester polyol is polytetramethylene ether polyol with a molecular weight of 2000.
[0022] The preparation method of the modified particles comprises the following steps: Step 1: After the graphene and cysteine solution are ultrasonically treated, the negative ion powder is slowly added, and after the addition is completed, ball milling is performed, and then filtering and drying are performed to obtain composite particles; Step 2: After isopropanol and cinnamaldehyde are stirred and mixed, thioglycerol and an initiator are added, and then subjected to ultraviolet irradiation treatment and rotary evaporation to obtain a modified monomer; Step 3: Mix the composite particles and the isopropanol solution, add the modified monomer after controlling the temperature, and stir to obtain modified particles; In step 1, the ultrasonic treatment is performed at a frequency of 350 W for 45 minutes; the ball milling is performed at 55 r / min for 1.9 hours; the drying is performed at a temperature of 80° C. to a constant weight; the mass ratio of the graphene, the cysteine solution and the negative ion powder is 9:45:1.9; the cysteine solution is prepared by mixing cysteine and deionized water at a mass ratio of 3.1:100; the negative ion powder is prepared by mixing magnesium tourmaline powder and magnetite metal powder at a mass ratio of 2.5:3.2; In step 2, the initiator is photoinitiator 1173; the thioglycerol is 1-thioglycerol; the mass ratio of isopropanol, cinnamaldehyde, thioglycerol and initiator is 7:13:7:0.33; the stirring and mixing is 450r / min stirring for 35min; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365nm for 1.8h.
[0023] In step three, the temperature of the temperature control is 22° C.; the stirring treatment is stirring at a speed of 250 r / min for 9 hours; the isobutanol solution is prepared by mixing isobutanol and deionized water in a mass ratio of 4:1; the mass ratio of the composite particles, isobutanol solution and modified monomer is 19:65:3.5. Example 3
[0024] A method for preparing a negative ion earplug composite material comprises the following steps: Step S1: in an inert atmosphere, polyester polyol, isocyanate, N,N-dimethylacetamide and a catalyst are stirred and mixed to obtain a premix; the inert atmosphere is a nitrogen atmosphere; the stirring and mixing is stirring at a speed of 800 r / min for 20 minutes; Step S2: adding the modified particles to the premix and subjecting it to constant temperature treatment, cooling it down and adding triethylamine and stirring it, thereby obtaining the product; the constant temperature treatment is to keep the temperature at 90° C. for 2.0 h; the cooling is to cool the temperature to 60° C.; the stirring treatment is to stir at a speed of 600 r / min for 50 min; In steps S1-S2, the mass ratio of the polyester polyol, isocyanate, N,N-dimethylacetamide, catalyst, modified particles and triethylamine is 58:33:2.2:3.3:15:5.0; the catalyst is dibutyltin dilaurate; the isocyanate is a mixture of HDI and MDI in a mass ratio of 1:2; the polyester polyol is polytetramethylene ether polyol with a molecular weight of 2000.
[0025] The preparation method of the modified particles comprises the following steps: Step 1: After the graphene and cysteine solution are ultrasonically treated, the negative ion powder is slowly added, and after the addition is completed, ball milling is performed, and then filtering and drying are performed to obtain composite particles; Step 2: After isopropanol and cinnamaldehyde are stirred and mixed, thioglycerol and an initiator are added, and then subjected to ultraviolet irradiation treatment and rotary evaporation to obtain a modified monomer; Step 3: Mix the composite particles and the isopropanol solution, add the modified monomer after controlling the temperature, and stir to obtain modified particles; In step 1, the ultrasonic treatment is performed at a frequency of 400 W for 50 minutes; the ball milling is performed at 60 r / min for 2.0 hours; the drying is performed at a temperature of 80° C. to a constant weight; the mass ratio of the graphene, the cysteine solution and the negative ion powder is 10:50:2.0; the cysteine solution is prepared by mixing cysteine and deionized water at a mass ratio of 3.2:100; the negative ion powder is prepared by mixing magnesium tourmaline powder and magnetite powder at a mass ratio of 2.5:3.3; In step 2, the initiator is photoinitiator 1173; the thioglycerol is 1-thioglycerol; the mass ratio of isopropanol, cinnamaldehyde, thioglycerol and initiator is 8:14:7.2:0.34; the stirring and mixing is 500r / min stirring for 40min; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365nm for 2.0h.
[0026] In step three, the temperature of the temperature control is 24° C.; the stirring treatment is stirring at a speed of 300 r / min for 10 hours; the isobutanol solution is prepared by mixing isobutanol and deionized water in a mass ratio of 4:1; the mass ratio of the composite particles, the isobutanol solution and the modified monomer is 20:70:4.
[0027] Comparative Example 1 Compared with Example 2, the difference in Comparative Example 1 is that cysteine is not used in step 1, and the other components, preparation steps and parameters are the same.
[0028] Comparative Example 2 Compared with Example 2, the difference of Comparative Example 2 is that cinnamaldehyde is not used in step 2, and the other components, preparation steps and parameters are the same.
[0029] Comparative Example 3 Compared with Example 2, Comparative Example 3 is different in that no thioglycerol is used in Step 2, and the remaining components, preparation steps and parameters are the same.
[0030] Comparative Example 4 Compared with Example 2, Comparative Example 4 is different in that no modified monomer is used in step 3, and the remaining components, preparation steps and parameters are the same.
[0031] Comparative Example 5 Compared with Example 2, the difference in Comparative Example 5 is that the mass ratio of the composite particles, the isobutanol solution and the modified monomer in step 3 is 19:65:6, and the other components, preparation steps and parameters are the same.
[0032] Comparative Example 6 Compared with Example 2, Comparative Example 6 is different in that ball milling is not performed in step 1, and the remaining components, preparation steps and parameters are the same.
[0033] The composite materials prepared in Examples 1-3 and Comparative Examples 1-6 were tested for the following properties, and the test results are shown in Table 1.
[0034] Mechanical properties test: A universal testing machine was used to test the cyclic compression and tensile properties of the specimens; the experimental compression rate was 500 mm / min, the compression strain was 75%, and the number of cyclic compressions was 30 times; the tensile strength test speed was 100 mm / min.
[0035] Table 1 Compression strength (MPa) Tensile strength (MPa) Example 1 62.8 6.2 Example 2 63.2 6.4 Example 3 62.6 6.1 Comparative Example 1 50.2 3.8 Comparative Example 2 52.7 4.0 Comparative Example 3 53.3 4.1 Comparative Example 4 46.8 3.3 Comparative Example 5 55.8 4.3 Comparative Example 6 54.2 4.2 From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the compressive strength and tensile strength of the composite materials prepared in Examples 1-3 of the present invention are significantly better than those of the composite materials in Comparative Examples 1-6.
[0036] Through the analysis of Examples 1-3 and Comparative Examples 1-6 in combination with Table 1, it can be seen that this is because the present invention allows cysteine to be attached to graphene through the action of hydrogen bonds and van der Waals forces, and then the agglomerated negative ion powder is further broken up by ball milling under the action of the mechanical force of the ball milling, thereby increasing the interface contact opportunity between the surface of the negative ion powder and cysteine, and utilizing the interaction between the thiol group on cysteine and the negative ion powder to promote more negative ion powder to adhere to the pore structure of the graphene, thereby achieving the sustained release effect of negative ions, and then by utilizing the click reaction between cinnamaldehyde and thioglycerol, carbon-sulfur bonds and large carbon atoms are introduced on cinnamaldehyde. The amount of hydroxyl groups, carbon-sulfur bonds and thiol groups have good affinity, which can promote the Schiff base reaction between the modified monomer and cysteine. During the Schiff base reaction, the introduction of hydroxyl groups in the modified monomer enables it to form hydrogen bonds and electrostatic adsorption with the carboxyl group of cysteine, forming a physical cross-linking hydrogen bond at one end, and connecting the other end through an imine bond formed between the amino group and the aldehyde group to form a self-repairing Schiff base compound, thereby improving the deformation recovery strength of the composite material, and finally realizing chemical and physical cross-linking, which can effectively coat the negative ion powder on the graphene, play a role in increasing the volume between the inorganic filler and the polyurethane system, and improve the mechanical properties of the composite material.
[0037] In addition, by grafting cysteine / cinnamaldehyde / thioglycerol on the modified particles and controlling the amount of modified monomers added, the amino groups are retained on the modified particles, so that the modified particles have both hydroxyl groups and amino groups, which can react with -NCO groups, thereby improving the interfacial bonding strength of the modified particles in the composite material system, introducing a large number of rigid benzene rings, significantly improving the cross-linking density of the polyurethane system, forming a denser network structure, and significantly improving its compressive strength and tensile strength.
[0038] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a negative ion earplug composite material, characterized in that: The preparation method comprises the following steps: Step S1: Under an inert atmosphere, polyester polyol, isocyanate, N,N-dimethylacetamide and a catalyst are stirred and mixed to obtain a premix; Step S2: adding the modified particles to the premix and subjecting to constant temperature treatment, cooling down and adding triethylamine and stirring to obtain; The preparation method of the modified particles comprises the following steps: Step 1: After the graphene and cysteine solution are ultrasonically treated, the negative ion powder is slowly added, and after the addition is completed, ball milling is performed, and then filtering and drying are performed to obtain composite particles; Step 2: After isopropanol and cinnamaldehyde are stirred and mixed, thioglycerol and an initiator are added, and then subjected to ultraviolet irradiation treatment and rotary evaporation to obtain a modified monomer; Step 3: Mix the composite particles and the isopropanol solution, add the modified monomer after temperature control and stir to obtain modified particles.
2. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step S1, the inert atmosphere is a nitrogen atmosphere; the stirring and mixing is stirring at a speed of 600-800 r / min for 15-20 min.
3. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step S2, the constant temperature treatment is to maintain the temperature at 80-90°C for 1.5-2.0h; the cooling is to cool to 50-60°C; and the stirring treatment is to stir at a speed of 500-600r / min for 40-50min.
4. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In steps S1-S2, the mass ratio of the polyester polyol, isocyanate, N,N-dimethylacetamide, catalyst, modified particles and triethylamine is 55-58:32-33:2.0-2.2:3.0-3.3:12-15:4.4-5.0; the catalyst is dibutyltin dilaurate; the isocyanate is a mixture of HDI and MDI in a mass ratio of 1:2; the polyester polyol is polytetramethylene ether polyol with a molecular weight of 2000.
5. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step one, the ultrasonic treatment is performed at a frequency of 300-400W for 40-50min; the ball milling is performed at 50-60r / min for 1.8-2.0h; the mass ratio of the graphene, cysteine solution and negative ion powder is 8-10:40-50:1.8-2.0; the cysteine solution is prepared by mixing cysteine and deionized water at a mass ratio of 3.0-3.2:
100.
6. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step 2, the thioglycerol is 1-thioglycerol; the mass ratio of the isopropanol, cinnamaldehyde, thioglycerol and initiator is 6-8:12-14:6.8-7.2:0.32-0.
34.
7. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step 2, the stirring and mixing is performed at a speed of 400-500 r / min for 30-40 min; and the ultraviolet irradiation treatment is performed at a wavelength of 365 nm for 1.5-2.0 h.
8. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step three, the temperature of the temperature control is 20-24° C.; the stirring treatment is stirring at a speed of 200-300 r / min for 8-10 hours.
9. The method for preparing a negative ion earplug composite material according to claim 1, characterized in that: In step three, the isobutanol solution is prepared by mixing isobutanol and deionized water in a mass ratio of 4:1; the mass ratio of the composite particles, the isobutanol solution and the modified monomer is 18-20:60-70:3-4.
10. A negative ion earplug composite material prepared by the preparation method according to any one of claims 1 to 9.